The Effect of Employees Competencies on Perceived Service Quality at Majlis Perbandaran Pulau Pinang - Kamalul Ariffin, Suhaida (2005)
The aim of the study is to investigate Service Quality perceived by employees in Majlis Perbandaran Pulau Pinang (MPPP) and also to examine the relationship between employee competencies and perceived service quality. Basically it is important to undertake this research, particularly at MPPP as Malaysia is now in position to enter a new stage of high employees competencies on the new era of globalization.